HUBUNGAN ANTARA PENGETAHUAN TENTANG ROKOK, TEMAN SEBAYA, ORANG TUA YANG MEROKOK, DAN IKLAN ROKOK TERHADAP PERILAKU MEROKOK PADA MAHASISWA AKADEMI KESEHATAN X DI RANGKASBITUNG - Sinaga, Sarma Eko Natalia (Coping: Community of Publishing in Nursing; Vol 4 No 2 (2016): Agustus 2016, 2016)
This research attempted to determine the relationship among  knowledge about smoking, peer group smoking behavior, parental smoking, , advertising influence and smoking behavior of Health Academy X in Rangkasbitung. The study was conducted with quantitative approach and used cross-sectional research design into total 94 (ninety-four) respondents. The result of the bivariate analysis using Chi-square test shows a significant relationship among knowledge about smoking (p = 0.004,? ? 0.05), peer group smoking behaviour (p = 0.000, ? ? 0.05) and smoking behaviour. Based on this research, is it recommended that lecturer enchance giving guidance to student about the bad effects of smoking, and impose a stict regulatin over smoking upon student. Parents need to give their children some understanding about the dangers of smoking. Keywords : Smoking Habit, Smoking Behavior, Teenagers